Improving pre-service science teachers’ creative thinking and innovative work production through a STEM-based biotechnology e-book - Indriyanti, Nor; Rahmah, Nur; Saputra, Risman; Habibi, Mohammad Wildan (Indonesian Journal of Science and Mathematics Education, 2026)
Biotechnology learning requires pre-service science teachers to translate concepts into design decisions grounded in creative thinking and innovation-oriented products. Yet, many resources remain content-centered and provide limited guidance for integrated STEM projects. This study developed and evaluated a STEM-based biotechnology e-book using a 4-D Research and Development model. Data were collected through expert validation, readability and practicality questionnaires, classroom observations, a creative thinking pretest and posttest analyzed using normalized gain, and an innovative work assessment rubric. The trials were conducted at a public university in Indonesia through a limited trial (n = 9) and a small-class trial (n = 19), followed by implementation at two universities (n = 30 each). The e-book showed very high validity (92-100%) and very practical ratings (89.63-91). Creative thinking improved substantially, for example, from 60.53 to 91.58 with an n-gain of 0.79 (high), and innovative work scores were consistently high (84 to 88). These findings indicate that project-centered STEM digital media can strengthen creative thinking and innovation outcomes in biotechnology teacher education. These findings imply that STEM-integrated biotechnology e-books embedding structured STEM projects can serve as transferable digital resources to support higher-order outcomes in science teacher preparation.